Two new species of fimicolous Pezizales (Ascomycota, Fungi) from a cleared Mexican tropical montane cloud forest - Alvarez-Cortés, Pedro Miguel; Raymundo, Tania; Luna-Vega, Isolda; Martínez-González, César Ramiro; Valenzuela, Ricardo; Martínez-Pineda, Michelle (Phytotaxa, 2026)
The fimicolous Mexican Pezizales are an interesting group of fungi for which there is a lack of adequate studies. Two new species of coprophilous Pezizales are described based on morphological, histochemical, and molecular characters from a cleared tropical montane cloud forest in western Mexico (Talpa, Jalisco), where they thrive in the excreta of cows and horses. This study utilizes certain histochemical characters as taxonomic markers to identify and distinguish the species. Iodophanus jaliscoensis Alv.-Cortés, R.Valenz. & Raymundo sp. nov. with paraphyses with carotenoid pigments that react with ferric sulfuric chloride (FeCl3-H2SO4), generating a sky blue hue (23C4), and Boubovia talpensis Alv.-Cortés, Mart.-Pineda & Raymundo sp. nov. with paraphyses with unsaturated derivatives of golden color (4C6) with potassium permanganate (KMnO4). Bouvobia species is a newly recorded genus in the TMCF and the country. This group of fungi is a crucial source of metabolites, and this research lays the foundation for future studies in taxonomy and biotechnology.